The effective utilization of internet bandwidth in organizational demand services and applications - Abubakar, Adamu; Wan Husin, Wan Nurul Izza (UiTM Press, 2022)
This research evaluates the sustainable utilization of Internet bandwidth usage and proposes a framework for its study. Understanding how much internet bandwidth is required for business and individual use and to what extend individual users have to be familiar with it, is very important. The study seeks to (1) measure the relationship between organizational learning and effective utilization of internet bandwidth; (2) assess the relationship between organizational learning and organizational performance; and (3) investigate the mediating effect of effective utilization of internet bandwidth in influencing the relationship between organizational learning and organizational performance. A reasonable sample population (n=318) is selected from those Malaysian business firms that use Internet bandwidth. Structural equation modeling (SEM) was utilized to test the relationship among study variables. Further analysis indicates that the results support certain hypotheses. Organizational learning is found to be of critical importance in the effective utilization of Internet bandwidth. However, the effective utilization of bandwidth does not mediate the effect of the relationship between organizational learning and organizational performance. This can be explained by the fact that learning the use of Internet bandwidth improves individual usage and better decision-making in choosing Internet bandwidth-demand-services and applications of an organization, yet does not significantly increase the operational and financial performance